Therapeutic potential of cannabinoids in neurological conditions: a systematic review of clinical trials - Hakami, Alqassem Y.; Alshehri, Fahad S. (Frontiers in Pharmacology, 2025)
OverviewCannabinoids have gained increasing attention for their therapeutic potential in treating several neurological conditions, including neurodegenerative diseases, chronic pain, and epilepsy. This review aims to assess the current clinical trials investigating cannabinoids, primarily Tetrahydrocannabinol and Cannabidiol, for neurological disorders. This review will aim to highlight the efficacy, safety, and outcome measures used in these trials.MethodsClinical trials were identified using ClinicalTrials.gov, focusing on studies that examined the effects of cannabinoids in treating neurological conditions. All trials that fulfilled the following criteria were included: Phase 1–4, focused on cannabinoids as primary intervention, and measured relevant outcomes such as pain relief, cognitive function, or spasticity reduction. Data on conditions, interventions, primary and secondary outcomes, and trial phases were extracted and analysed.ResultsA total of 47 clinical trials were identified, including different neurological conditions. The most frequently studied conditions were Multiple Sclerosis, Fibromyalgia, and Parkinson’s Disease. Most trials were in Phase 2, with the primary outcome measures focused on pain management, spasticity, and cognitive function. Secondary outcomes included safety and tolerability measures.ConclusionThe review highlights the broad therapeutic potential of cannabinoids in neurology, with promising results in symptom management for conditions like Multiple Sclerosis and Fibromyalgia. However, the lack of standardized study protocols, dosing, and outcome measures presents challenges for broader clinical implementation.Systematic Review Registrationclinicatrials.gov.